EXPERIENCE OF THE MATERNAL WEANING PROCESS AMONG PRIMIPAROUS WOMEN: QUALITATIVE STUDY - Silva, Duiliane Coêlho e; Brito, Mychelangela de Assis; Carneiro, Cristianne Teixeira; Rocha, Ruth Cardoso; Rocha, Karla Nayalle de Souza; Dantas, Amanda Lúcia Barreto; Bezerra, Maria Augusta Rocha (Cogitare Enfermagem, 2023)
Objective: To understand the experience of the weaning process for primiparous mothers in a municipality in the interior of Ceará, Brazil. Method: Using semi-structured interviews, a descriptive, qualitative study was conducted with eight women. Data collection from August 2022 to March 2023 in Primary Health Care, using Bardin's content analysis. Results: three thematic categories emerged: reasons for the mother's decision to wean, strategies employed by the mother to wean, and the consequences of weaning for the mother and child. Maternal perceptions of the motivation for weaning were related to behavioral aspects of the child and maternal needs. Various strategies were classified as gradual or abrupt weaning, which generated changes in the children's behavior and contradictory feelings in the mothers. Final considerations: weaning is experienced unpleasantly, generating suffering. It reveals the lack of professional assistance and the need to expand studies.